2006
DOI: 10.1207/s15327558ijbm1303_9
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue varies by social class in african americans but not caucasian americans

Abstract: Socioeconomic status explains many ethnic disparities in health; however, mechanisms are hard to identify. Fatigue-a frequent complaint in patients and normals-is associated with poorer quality of life. We wondered if ethnicity and social class interact to explain fatigue. A total of 40 African Americans (AAs) and 64 Caucasian Americans (CAs) completed short forms of the Profile of Mood States (POMS-SF) and Multidimensional Fatigue Symptom Inventory (MFSI-SF). Participants were divided into high-middle and low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 35 publications
0
13
1
Order By: Relevance
“…Based on past reports, we hypothesized that both Blacks and individuals of lower SES would have shorter and poorer sleep, as characterized by shorter sleep duration, poorer sleep continuity, less Stage 3 to 4 sleep, and more complaints on self-report measures. In addition, we explored whether an interaction exists between race and SES in association with sleep, as has been the case with a variety of other health outcomes (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…Based on past reports, we hypothesized that both Blacks and individuals of lower SES would have shorter and poorer sleep, as characterized by shorter sleep duration, poorer sleep continuity, less Stage 3 to 4 sleep, and more complaints on self-report measures. In addition, we explored whether an interaction exists between race and SES in association with sleep, as has been the case with a variety of other health outcomes (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, only one study has assessed the associations among SES, race/ethnicity, and fatigue using both a unidimensional measure of fatigue and the MFSI-SF. The study found that while there were no differences in unidimensional fatigue or the MFSI-SF general fatigue subscale as a function of social class among Whites, middle-to-high SES African Americans reported significantly more fatigue than their White counterparts and than low SES African Americans (Bardwell et al 2006). No racial/ethnic or SES differences were noted for the other MFSI-SF subscales (Bardwell et al 2006).…”
Section: Introductionmentioning
confidence: 82%
“…The study found that while there were no differences in unidimensional fatigue or the MFSI-SF general fatigue subscale as a function of social class among Whites, middle-to-high SES African Americans reported significantly more fatigue than their White counterparts and than low SES African Americans (Bardwell et al 2006). No racial/ethnic or SES differences were noted for the other MFSI-SF subscales (Bardwell et al 2006). Overall, additional research is needed to better understand demographic variations in the fatigue experience of African American community members.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations